The Influence of Gender Role and Women’s Empowerment on Couples’ Fertility Experiences: A Comprehensive Review - Mashael Ayesh Bumozah et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Abstract Gender roles and women’s empowerment play a pivotal role in shaping couples’ fertility experiences, including decision-making, family size, and reproductive health outcomes. Traditional gender norms often place women in subordinate positions, influencing their ability to make autonomous reproductive choices. Women’s empowerment—defined as access to education, employment, decision-making power, and healthcare—has emerged as a critical factor for fertility preferences and family planning. This review explores how gender roles and women’s empowerment intersect to impact fertility experiences and provides evidence from recent studies on their outcomes. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/281 https://doi.org/10.5281/zenodo.14497919